The contribution of the Basic Education Assistance Module in enhancing access to education in Gutu District, Zimbabwe - Kanengoni, Joice (My University, 2021)
This study explored the contribution of the Basic Education Assistance Module (BEAM) in enhancing access to education in Gutu District, Zimbabwe. BEAM is the largest social protection programme in Zimbabwe, the programme provides educational assistance, in form of school and examination fees, for orphans and vulnerable children (OVCs) who have never been to school, who are likely to drop out of school and those who have dropped out of school. The objective of the programme is to alleviate poverty through enhancing access to education. Despite the fact that BEAM has been providing educational assistance for the past two decades, there is lack of literature on the lived experiences of BEAM beneficiaries. It is against this background that this study sought to explore BEAM. This study was guided by seven objectives namely: to establish the profiles of parents/guardians/caregivers and beneficiaries of BEAM in Gutu District, Zimbabwe; to explore the experiences of parents/guardians/caregivers of beneficiaries on the selection process and the provision of the BEAM; to explore the perceptions of the parents/guardians/caregivers of BEAM beneficiaries about the contributions of the programme in enabling beneficiaries to access education and remain in school; to explore educators’ experiences when operationalising BEAM to beneficiaries in Gutu District, Zimbabwe; to determine the challenges associated with the provision of BEAM in Gutu District, Zimbabwe; to explore the perceptions of government officials about the implementation of BEAM in Gutu District, Zimbabwe and to develop guidelines to enhance the usefulness of BEAM in Gutu District, Zimbabwe. To achieve the stated objectives, a qualitative research approach was adopted in the study; a case study design was used. The study population consisted of 60 parents/guardians/caregivers of the beneficiaries of BEAM and 8 key informants who consisted of 6 educators who were responsible for managing BEAM, the District Remedial Tutor and the head of the Department of Social Welfare in Gutu District, Zimbabwe. Purposive sampling was used to select participants. Data was collected using separate semi-structured interview schedules for participants and key informants. In-depth face to face interviews were used to collect data. Data was analysed using thematic analysis. The findings of the study revealed that attaining basic education remains a major challenge for OVCs, particularly those who reside in rural areas characterised by extreme poverty. It emerged that BEAM made a notable contribution in enhancing access to education for OVCs. The study showed that children who were eligible for BEAM benefits were single and double orphans, disabled children, children from low income families and children under the care of individuals who were old aged, chronically poor and ill health. Additionally, the findings of the study revealed that community members took a leading role in selecting BEAM beneficiaries. While principals, deputy principals, and educators participated in the nomination of BEAM beneficiaries, they were not involved in their selection. The findings of the study revealed that the implementation of BEAM was informed by gender equity, the selection of BEAM beneficiaries and members of Community Selection Committee (CSC) was informed by the principle that at least 50% of them should be females. The challenges that are associated with the provision of BEAM are notable to this study. It emerged that BEAM applications were carried out on annual basis, this was a major inconvenience for disabled and old aged parents/guardians/caregivers who had to walk long distances to the selected schools to renew applications, also, yearly applications led to the removal of beneficiaries from BEAM before attaining basic education. The findings of the study indicated that BEAM was less comprehensive in addressing the educational needs of beneficiaries as benefits were limited to school fees and half of examination fees, while complementary benefits including school uniforms, meals and books were not covered on the programme. The findings of the study showed that not all eligible children were on BEAM due to the underfunding of the programme, also, the inconsistences that characterised the provision of BEAM led to beneficiaries dropping out of school. Drawing from its findings, the study proposes that skills building programmes should be implemented to equip parents/guardians/caregivers of beneficiaries of BEAM with skills which enable then to generate income and become better equipped in meeting their needs. Additionally, the study proposes that BEAM applications should be once off, to eliminate the possibility of beneficiaries being removed from the programme before attaining education. The study recommends that there should be improved budgetary allocations for BEAM, to ensure that all eligible children benefit from the programme and to ensure the provisions of full examination fees, books, school uniforms and meals on BEAM. The study calls for the inclusion of educators, principals and deputy principals in the selection of BEAM beneficiaries, it is envisaged that the knowledge they possess on the experiences of children will allow for the selection of most eligible children. On addition the study proposes that there should be student representatives for BEAM beneficiaries, who communicate with responsible authorities regarding the needs and concerns of BEAM beneficiaries, this will promote the social inclusion of beneficiaries in the development of their communities. Given that beneficiaries of BEAM were children who suffered vulnerabilities associated with losing parents through death, the study proposes that counselling services should be made available for BEAM beneficiaries and their families. This study expanded knowledge and understanding of the contributions of BEAM in enabling OVCs to access education. This study contributed to the development of guidelines to enhance the usefulness of BEAM. On addition, the study expanded social work knowledge on social protection and education, which helps to improve the existing support services for vulnerable members of society
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Social Work at the University of the Witwatersrand, 2021